Association of lean body mass to menopausal symptoms: The Study of Women's Health Across the Nation - Rosanne Woods; Rebecca Hess; Carol Biddington; Marc Federico (BMC, 2020)
Abstract Background The purpose of this study was to examine the association of lean body mass (LBM) to the development of vasomotor symptoms (VMS) as women transition through menopause. Methods This study is a secondary use of data available for public use from follow up visits six through 10 for participants in the Study of Women's Health Across the Nation. The study examined 2533 women, between the ages 42-52 years, each year over a10-year period. Data was modeled for associations of lean body mass and VMS. Changes in LBM since prior visit and since baseline were also modeled along with differences in means using binary logistic regression, adjusting for covariates. Results LBM was significantly associated to concurrent VMS (p = .036), percent change in LBM since prior visit (p = .003), percent change since baseline (p < .001), and overall means associations (p = .023). LBM was not significant for VMS at individual visit measures. In mixed regression modeling, time was significant (p < .0001) at all visits. The estimated probability of developing VMS decreases significantly as LBM increases. Conclusions Lean body mass is negatively associated with incident VMS. Our data suggests that maintaining higher levels of LBM during the menopausal transition may be protective against the development of VMS. Every woman will experience menopause in her life and the ability to potentially prevent the onset of specific symptoms through basic interventions, such as resistance training to increase lean body mass, may positively impact this large population.